2004
DOI: 10.1080/00071660412331286208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementary iodine on the performance and egg traits of laying hens

Abstract: 1. This experiment was carried out to determine the effects of dietary iodine supplementation on the performance and egg traits of laying hens. A total of 600 SHSY type brown layers aged 21 weeks of age were chosen at random from a large flock. They were randomly distributed into 30 pens at 20 hens per pen. Each treatment comprised 6 replicates of 20 layers in groups of 5 birds. The diets were supplemented with 0, 3, 6, 12 and 24 mg/kg iodine as calcium iodate. The experimental period lasted 30 weeks. 2. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 7 publications
6
16
2
Order By: Relevance
“…In agreement with the present study, some researchers reported that I supplementation to layer hens diets had no significant effects on egg production, egg mass production, egg weight, feed intake, FCR, un‐normal eggs and body weight changes (Lichovnikova & Zeman, ; Opaliński et al., ; Yalçin, Kahraman, Yalcin, Yalcin, & Dedeoglu, ).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with the present study, some researchers reported that I supplementation to layer hens diets had no significant effects on egg production, egg mass production, egg weight, feed intake, FCR, un‐normal eggs and body weight changes (Lichovnikova & Zeman, ; Opaliński et al., ; Yalçin, Kahraman, Yalcin, Yalcin, & Dedeoglu, ).…”
Section: Discussionsupporting
confidence: 92%
“…The tested concentrations showed no significant impact on hen performance (Tables 3 and 5), which confirmed other studies (Richter 1995;Yalc¸in et al 2004). However, potential long-term effects, as found by and Lichovnikova et al (2003), were not tested in the present study.…”
Section: Influence Of Iodine Supply On Hen Performancesupporting
confidence: 93%
“…Iodine contents of 0.8, 2.9, 5.2, 11.1 and 21.5 mg kg -1 layer diet resulted in 48, 107, 180, 290 and 511 µg iodine kg -1 egg albumen, and 443,664,1122,1953 and 3352 µg iodine kg -1 egg yolk, respectively (Yalçin et al, 2004).…”
Section: Eggsmentioning
confidence: 99%
“…Iodine from eggs is calculated based on the data of Yalçin et al (2004). For layer diets containing 10 mg iodine kg -1 , the experimental data obtained with 11.1 mg iodine kg -1 are used, for 5 mg iodine kg -1 , the data obtained at 5.2 mg iodine kg -1 .…”
Section: The Contribution Of Iodine-supplemented Feeds To Human Dietamentioning
confidence: 99%
See 1 more Smart Citation